Pembelajaran Tari (Tatak) Tintoa Serser melalui Media Audio Visual untuk Siswa SMA Swasta Daerah Sei Bejangkar - Lailatul Fitria Pane (Universitas Negeri Medan, 2016)
This research was about learning cultural art esspecially dance art thetopic was Tatak Tintoa Serser can be effective and efficient by using audiovisual.In this research was using the theoriticals its relation with topicresearch about audio visual method and to result of theory practiced.Thismethod was using descriptive quantitative. The population this methoddirectly was the sample of SMA Swasta Daerah Sei Bejangkar. Tekhnik tocollected data were research, library study, documentasi, and tes ofpractice.Based on the research, this research was using audio visual as a helptools to learnt who give result included psicimotoric value, the student wassuccess 83,33% and the student was not success 16,66%. The attitude ofstudy result get the best value was 26,67%, the student get better value was40%, and the student get anough value was 33,33%. The kognitive of studyresult get the best value was 26,67%, the student get better value was 40%,and the student get anough value was 33,33%. By using audio visual methodof learning Tatak Tintoa Serser more effective and efficient.